VOx‐Based Non‐Volatile Radio‐Frequency Switches for Reconfigurable Filter - Dabin Seo; Dahyeon Kim; Jiyeon Ryu; Changwoo Pyo; Seungchan Lee; Tae‐Sik Yoon; Myungsoo Kim (Advanced Science)
Abstract Vanadium oxide (VOx) based memristor is a promising candidate for next‐generation non‐volatile memory and radio‐frequency (RF) switches due to its compatibility with wafer‐level integration and high‐frequency operation. This work demonstrates high‐performance VOx memristor with gold and silver electrodes, achieving a higher cutoff frequency compared to previously reported VOx devices. The devices exhibit long retention, high endurance (≈103 cycles), and nanosecond switching speeds, enabling the fabrication of RF switches with a cutoff frequency of ≈4.5 THz, low insertion loss (< 0.46 dB), and high isolation (>20 dB) from 0.1 to 20 GHz with stable operation extended to frequency up to 67 GHz. Leveraging these switches, a reconfigurable X‐band bandpass filter whose is realized center frequency is tuned from 8.2 GHz in the OFF state to 7.6 GHz in the ON state, achieving a tunable range of ≈600 MHz. This demonstration paves the way for compact and versatile RF front‐ends with improved frequency agility in advanced communication systems.